Governance of Community Learning Centers in Indonesia: A Systematic Literature Review - Dadang Yunus Lutfiansyah Dadang; Hanifah Irnawati; Yanti Shantini; Ihat Hatimah; Aqeel Khan (Journal of Nonformal Education, 2026)
Background - Community Learning Centers (PKBM) serve as critical non-formal education institutions in Indonesia, yet governance challenges persist across leadership, collaboration, accountability, policy alignment, and digital dimensions. Research Urgency - Despite growing research on PKBM, a comprehensive synthesis focusing specifically on governance dimensions remains limited. Post-pandemic digital transformation introduces new governance dynamics requiring systematic analysis. Research Objectives - This study aims to: (1) systematically review literature on PKBM governance in Indonesia; (2) identify key governance dimensions influencing implementation; (3) develop an integrated multi-level governance framework; (4) identify critical challenges; and (5) provide evidence-based recommendations. Research Method - Following the PRISMA framework, 18 studies from Google Scholar, Scopus, and ERIC (2022–2026) were analyzed using a multi-level governance theory. Thematic analysis employed an integrated deductive-inductive approach. Research Findings - Results reveal five key governance dimensions: transformational leadership capacity, multi-stakeholder collaboration, accountability mechanisms, policy alignment, and digital governance. Cross-study synthesis identifies three structural contradictions: the standardization-flexibility paradox, the accountability pluralism dilemma, and the digital equity tension. Research Conclusion - Governance plays a decisive role in shaping PKBM effectiveness, quality, and sustainability. The integrated multi-level framework illustrates complex interdependencies across micro, meso, and macro governance levels, advancing governance theory for community-based non-formal education in developing country contexts. Research Novelty/Contribution - This study provides the first comprehensive multi-level governance framework specifically tailored to community-based non-formal education in developing country contexts, synthesizing fragmented literature into a coherent theoretical model and offering evidence-based policy recommendations for strengthening inclusive lifelong learning ecosystems.